Judges Against Justice: On Judges When the Rule of Law is Under Attack - Graver, Hans Petter (Springer, 2016)
This book explores concrete situations in which judges are faced with a legislature and an executive that consciously and systematically discard the ideals of the rule of law. It revolves around three basic questions: What happen when states become oppressive and the judiciary contributes to the oppression? How can we, from a legal point of view, evaluate the actions of judges who contribute to oppression? And, thirdly, how can we understand their participation from a moral point of view and support their inclination to resist?